Problems of Standard Model, Review - Paudel, Eak Raj (BMC Journal of Scientific Research, 2021)
It is assumed that standard model is the most successful theory of particle physics but it is not perfect. In this paper, I am interested to flash the published results of various proposals of theoretical physicists in various modes of Standard Model and beyond. There are no specifications theory to declare new model to till date, although some ideas that would modify the standard model in many ways helps to understand the existing results.